The English Version of the Multidimensional Inventory for Religious/Spiritual Well-Being (MI-RSWB-E): First Results from British College Students - Human-Friedrich Unterrainer; Oliver Nelson; Joanna Collicutt; Andreas Fink (Religions, 2012)
In recent years there has been a steadily growing interest of religious/spiritual issues in several areas of psychology; a variety of reliable and valid means of assessing the different facets of religiosity/spirituality have been developed. However, there is still some need for multidimensional approaches. With respect to the positive experience with the German version of the Multidimensional Inventory for Religious/Spiritual Well-Being, we developed an English version of this scale (MI-RSWB-E) in order to facilitate research in this budding field. The MI-RSWB-E was tested and validated on a sample of British college-students (n = 400). First, the factor structure and psychometric properties of the MI-RSWB-E were analysed. As a second step, MI-RSWB-E dimensions were related to a variety of indicators of personality and mental health. An in-depth analysis provided evidence in support of the psychometric quality of the MI-RSWB-E, and the ability of its proposed six-factor structure. The MI-RSWB-E dimensions were also found to be substantially related to personality factors as well as with indicators of subjective well-being and mental illness. In light of these findings the MI-RSWB-E could be considered as a suitable tool in the assessment of different facets of religiosity/spirituality.